Factors influencing players to purchase in-game content - Gaurav Sharma (International Journal of Advanced Science and Technology, 2020)
Research shows that the gaming industry is one of the most booming industries in the world. Today, the most successful revenue model for all game developers is selling in-game content. The reasons which drive these players to purchase such in-game content are game boosters, bonus coins, additional features, character modification, purchasing in-game artifacts and virtual assets. The sample size of this analysis is 150. Study reveals that these additional features that these gamers get after purchasing the in-game content motivates them to continue the game further. These value additions act as a driving force towards satisfaction. It has been seen through the research that game type determines the intent to purchase virtual goods. Factors which influence players to purchase in-game content for endless running 3-D video games are survival advantages, bonus points, extra lives, speed boosters. In case of strategy-based war games, the factors which are utility, playfulness, extra artifacts, time reduction in case of level up.  More than the storyline and graphics of the game these purchasable in-game content drives the players to continue playing that game. Game developers continue to make additions in games to retain players. In fact, many developers have created an innovative virtual asset called passes which provides additional features for a specific time period.Keywords: in-game content, online gaming, virtual assets.